Treatment patterns and outcomes in BRAF V600E‐mutant melanoma patients with brain metastases receiving vemurafenib in the real‐world setting. (20th May 2015) - Gibney, Geoffrey T.; Gauthier, Geneviève; Ayas, Charles; Galebach, Philip; Wu, Eric Q.; Abhyankar, Sarang; Reyes, Carolina; Guérin, Annie; Yim, Yeun Mi
<x xml:space="preserve">Abstract</x> This retrospective study used data reported by US oncologists from patient charts to provide information on real‐world treatment patterns and clinical outcomes of patients with BRAF V600E‐mutant melanoma brain metastases (MBM) treated with vemurafenib. Following vemurafenib initiation, 48.1% of patients experienced intracranial response and 45.6% experienced extracranial response. Overall survival rate at 12 months was 59.0%. Analyses showed associations between intracranial response and both corticosteroid use and vemurafenib as initial therapy after MBM diagnosis. Larger size and number of brain metastases and progressive extracranial disease at the time of treatment initiation were associated with decreased intracranial response and increased risk of disease progression. Multiple extracranial sites and the absence of local treatments were also associated with increased risk of progression. Finally, multiple extracranial disease sites, progressive extracranial disease, and larger number of brain metastases were associated with an increased risk of death. <boxed-text content-type="graphic" id="cam4475-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>